Effect of Return on Assets (ROA) and Leverage Ratio on Company Value of PT. MNC Land Tbk - Wisnu Uriawan; Iwan Permana (Fakultas Ekonomi dan Bisnis Islam, 2022)
Business competition in the world is getting tougher, companies are required to improve company performance for the better. With that the company must have a financial report every year, so that it can know the turnover of working capital and generate profits on the use of the company's own capital. The purpose of this study was to determine and analyze the effect of ROA and LR on firm value either partially or simultaneously at PT. Indofarma Tbk. In this study using descriptive analysis with a quantitative approach. Based on the results of the study, it was found that partially Return On Assets (ROA) had a positive effect on firm value as indicated by a coefficient of determination of 20.2%. Partially Leverage Ratio has no positive effect on firm value with a coefficient of determination of 0.1%. Then simultaneously Return On Assets (ROA) and Leverage Ratio have a positive effect on Firm Value with a coefficient of determination of 20.8% at PT MNC Land Tbk.